Transformasi Kinerja Karyawan melalui Penerapan Sistem Informasi Manajemen yang Efisien - Indrawati; Mintawati, Hesri; Simangunsong, Bonse Aris Mandala Putra; Safrila, Annisa; Darmariani, Martiana Kusuma; Zein, Reza Maulana (JUDICIOUS, 2023)
Transforming employee performance through the implementation of efficient management information systems has become a major focus in modern management literature. The literature study highlights the importance of efficient integration of management information systems in increasing employee productivity and performance. Previous research shows that the implementation of efficient management information systems can provide significant benefits, such as increased data accessibility, faster decision making, and improved coordination between business units. In addition, the literature also highlights the important role of information technology in facilitating the employee performance transformation process. With the adoption of the right technology, organizations can improve business processes, reduce the time required for administrative tasks, and increase overall operational efficiency. In this context, the literature study emphasizes the importance of integrating management information systems with existing business strategies to achieve optimal results. However, research also highlights some of the challenges that may be faced in implementing an efficient management information system, including resistance to change, high implementation costs, and a lack of understanding of its benefits. Therefore, a good understanding of organizational needs, support from leadership, and appropriate training for employees are key factors in the successful implementation of an efficient management information system. Overall, the literature study confirms the importance of implementing efficient management information systems in improving employee performance and providing competitive advantages for organizations in this digital era. With a good understanding of the benefits, challenges and effective implementation strategies, organizations can harness the full potential of employee performance transformation through the implementation of efficient management information systems.